Associação espaço-temporal entre mortalidade por neoplasiase proximidade de antenas de telefonia celular em Belo Horizonte - Vanessa Loureiro Silva (2012)
With the development of technology and communications, sources of electromagnetic fields (EMFs) created by humans increased considerably. There is increasing evidence about the potential health risks associated with these fields, since humans are bioelectricalsystems and may interact with radiation. Few studies have been conducted specifically considering the cell phone base stations as a source of electromagnetic radiation. Residents in the surroundings of the antennas of the cellular telephone system are more susceptibleto exposure to EMF and should be observed. In her thesis completed in 2010, Adilza Dode investigated, descriptively, the correlation between the location of base stations and cases of deaths from neoplasms (cancers) in the city of Belo Horizonte, in the period 1996 to 2006. In this work, we will continue to Dodes thesis, using analysis techniques ofBivariate Point Processes, but will be considered only deaths from the year 2000 (after installing the antennas). Moreover, we geocode deaths from cancer unrelated to electromagnetic radiation occurred in the city during the same period, to be taken as Controls. Given the need to formally investigate the interaction of cellular antennas with deaths inboth Cases and Controls, we made two changes in the Kt12 function proposed by Pinheiro (2009), which tests the independence of spatiotemporal two point processes, but whose alternative hypotheses do not meet the criteria required in the application under study. By the second proposed amendment, Kt(2) 12 function, we find evidence of an positives patial interaction and negative temporal interaction between Antennas and Cases, which increases with increasing exposure time T, as also between Antennas and Controls, although more modest and weaker with increasing time T. The results are a motivationfor further studies of association between cancer and cell phone antennas.